Enfeksiyon Hastalıkları ve Klinik Mikrobiyoloji-Güz - Benli, Aysun; Özdemir, Yeliz; Özmen, Cumhur; Demirci, Melis; Gezer, Yakup; Yüce Yıldırım, Deniz; Geyiktepe Güçlü, Ceyda; Güçlü, Kadir Görkem; Borcak, Deniz; Yörük, Gülşen (2024)
-